Analisis Audit Sistem Informasi Berbasis Cobit 5.0 Website Pengembangan Karir dan Kewirausahaan - Regina Josephine; theresiawati, theresiawati; Henki Bayu Seta; I Wayan Widi Pradyana (SOTVI - Society of Visual Informatics, 2025)
The Technical Implementation Unit for Career Development and Entrepreneurship (UPT PKK) UPN Veteran Jakarta is a facility for students to obtain information related to entrepreneurship and career opportunities. However, the utilization of the UPT PKK UPNVJ website is considered suboptimal, with 71% of respondents stating that the website services still require improvement. This research aims to improve the quality of the UPT PKK UPNVJ website feature services through an information system audit using the COBIT 5.0 framework in the APO, BAI, and DSS domains. The subdomains analyzed include APO (APO01, APO11, APO13), BAI (BAI02, BAI09), and DSS. (DSS01, DSS03). The audit results show an average capability score of 3.78, which falls within the Predictable Process level, with a gap of 0.14 from the expected level. In-depth analysis reveals that the IT processes in the APO11 and APO13 subdomains have a gap of 1 from the expected level, which is level 5. This study concludes that although most processes have met a good level of capability, there are opportunities for improvement in several subdomains to reach the expected level of capability. Improvement recommendations are focused on optimizing IT processes in the APO11 and APO13 subdomains to enhance the overall performance of the UPT PKK website.